Development of Nitrate-Nitrogen Calibration Curve Using Laboratory Resistivity Method in Acidic pH Condition - M.Fadzli, M.Aizuddin; Wan Mohamed, Wan Afnizan (Recent Trends in Civil Engineering and Built Environment, 2023)
A laboratory experiment was carried out to determine the resistivity value of various concentrations of nitrate-nitrogen in acidic solutions with pH values ranging from 2 to 6.2. The purpose of this study is to get the quantitative analysis of nitrate nitrogen calibration curve at acidic pH condition by performing resistivity method. A series of nitrate-nitrogen covering three range namely low (2mg/L to 10mg/L), medium (20mg/L to 100mg/L), and high (200mg/L to 1000mg/L). Were prepared in acidic condition and was tested using resistivity meter box to obtain the associated resistance value. The resistivity value was calculated by multiplying the resistance reading obtained from resistivity meter box with multiplier factor of 10 at several acidic condition (pH 2 to 6.2). The results in this lab experiment show that the concentration of the nitrate-nitrogen is inversely proportional to the resistivity value. This is because the high number of ions will result in the high conductivity and low resistivity. The calibration curves that have been obtained including R2 value that showing its closer to 1.000. Thus, it can be referred that the calibration curve provided a great details and references as data collected was quite accurate.